Perancangan Charger Untuk Baterai Lithium Polymer Smart Phone Dengan Kapasitas Arus 4a Pada Tegangan Baterai 3,7v - Rahmat Faisal Wahyudi; Sigit Yuwono; Estananto Estananto (eProceedings of Engineering, 2018)
Abstrak Baterai jenis lithium sangat dibutuhkan untuk kebutuhan perangkat elektronik pada era digital sekarang ini. Perangkat elektronik pada era digital sekarang biasanya membutuhkan baterai berkapasitas besar. Dengan besarnya kapasitas baterai tersebut, dibutuhkan sebuah charger yang dapat mengisi ulang baterai dengan waktu relatif cepat. Salah satu solusinya adalah sebuah charger yang dapat memberikan arus besar. Pada TA ini, charger dirancang untuk baterai jenis lithium polymer yang memiliki tegangan minimal sebesar 3,7V saat baterai kosong dan 4,3V saat baterai penuh. Ketika tegangan terdeteksi sebesar 3,7V maka arus yang mengalir sebesar 4A, dan ketika tegangan baterai sebesar 4,3V maka arus yang mengalir mendekati 0A. Pada perancangan charger ini diharapkan dapat mempercepat waktu pengisian baterai lithium polymer dua kali lipat dari biasanya (Quick Charge). Charger ini diharapkan dapat memberikan arus maksimal berkapasitas 4000mAh pada tegangan 3,7V. Hasil yang dituju adalah sistem pengisian baterai berkapasitas besar yang cepat dan aman tanpa adanya kerusakan akibat tegangan dan arus berlebih. Kata Kunci : Charger, Quick Charge, Regulator, Arus Maksimal. Abstract In this digital era, Lithium-type batteries are needed to be widely used on electronic devices. In order to accommodate the needs of this digitalized world, the electronic devices must be supported by long-life battery in the other word is large capacity battery. That large capacity battery would need a charging system that capable to re-charge the battery in a short amount of time. In order to do that, a charger that can provide high voltage and high current are necessary, with note the voltage and current level must comply with the maximum of the battery power level to avoid any battery damage such as explosion. This charger is designed for lithium polymer type battery which has minimum voltage 3.7V as it is in empty condition and 4.2 as it is in full condition. When the voltage is detected at 3.7V the current is flowing at 4A, and when the battery voltage is 4.2V then the current flowing is very small or in other words no current is flowing. Voltage and current settings are performed by any regulator that is capable of passing high currents. In designing this charger to speed up charging time of lithium polymer battery twice than usual (Quick Charge). The charger is capable to deliver maximum current for battery with the capacity of 4000mAh. The result is a fast and secure large capacity battery charging system without any damage due to over-voltages and currents. Keywords : Charger, Quick Charge, Regulator, High Current